Special exercises to improve flexibility in female artistic gymnastics athletes/Ejercicios especiales para mejorar la flexibilidad en las atletas de gimnasia artística femenina - Marlen Echevarria Pérez; Yolainy Govea Díaz; Zaily Armenteros Vázquez; Yardleys Noda Rabelo; Melix Ilisástigui Avilés (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
This study begins when detecting that, in the flexibility physical tests, the artistic gymnastics athletes of the 6-8 years old category of the municipality of Pinar del Río present difficulties that bring with them little amplitude, harmony and aesthetics in the technical elements that they perform. Among the tests performed in the pioneer championship, one of them is to measure the level of flexibility, since it is a key element in the learning of techniques, which enables the joints to perform a maximum range and adopt different positions. Given this situation, it was proposed as an objective in this research to elaborate special exercises for the improvement of flexibility in athletes of the 6-8 years old category. For this purpose, theoretical methods such as analysis-synthesis, induction-deduction and empirical were used, specifically the review of documents, observation and measurement, which facilitated the research process. This study was conducted with the four coaches of the female artistic gymnastics specialty and the 4 athletes of the 6-8 years old category. The special exercises include aspects necessary for the athletes to be able to execute the tests without difficulties, that is, with a previous mastery and to obtain better results. This work offers the trainers special exercises that allow them to improve the flexibility training process, specifically in the ages covered by the research.